A Mesomechanical Analysis of the Deformation and Fracture in Polycrystalline Materials with Ceramic Porous Coatings - Balokhonov R. R. Ruslan Revovich; Zinoviev A. V.; Romanova V. A. Varvara Aleksandrovna; Batukhtina E. E. (2015, 2015)
Title screen